ANALISA USAHA BUDIDAYA PEMBESARAN IKAN LELE DI KECAMATAN BULELENG - Wira Arsana, Komang Agus; I Nyoman Dodik Prasetia; Alexander Korinus Marantika (JURNAL LEMURU, 2023)
The objectives of this study are to: 1) calculate the cost of raising catfish in Buleleng District; 2) calculate the revenue and profit from raising catfish in Buleleng District; and 3) evaluate the viability of the catfish-rearing industry in Buleleng District as measured by the R/C Ratio, Payback Period (PP), and Break Even Point (BEP). The research method used is descriptive quantitative research. Interviews, documentation, and literature reviews are the data collection techniques employed. The findings revealed that: 1) Catfish rearing costs in Buleleng District range from IDR 2,498,125 to IDR 10,414,573. 2) The receipt of catfish enlargement farming business costs between IDR 3,150,000 and IDR 16,800,000, and earnings between IDR 2,607,500 and IDR 25,541,708 (in Indonesian rupiah). 3) Analysis of the catfish enlargement farming industry in Buleleng District. The R/C ratio runs from 1.2 to 1.6 per rupiah, the payback period ranges from 4.7 to 7.8 months, and the break event threshold ranges from Rp 13,018/kg to Rp 16,654/kg. According to the findings of the business feasibility analysis study, it is viable to carry out catfish cultivation expansion in the Buleleng District